2016
DOI: 10.1002/ece3.1934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyploidy and reproductive mode on life history trait expression

Abstract: Ploidy elevation is increasingly recognized as a common and important source of genomic variation. Even so, the consequences and biological significance of polyploidy remain unclear, especially in animals. Here, our goal was to identify potential life history costs and benefits of polyploidy by conducting a large multiyear common garden experiment in Potamopyrgus antipodarum, a New Zealand freshwater snail that is a model system for the study of ploidy variation, sexual reproduction, host–parasite coevolution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 80 publications
1
46
0
Order By: Relevance
“…A stoichiometric perspective leads us to speculate that genome size and ploidal level are important but often ignored functional traits. For example, very large genomes in plants could be selected against in many ecosystems due to their higher demands for N and P. In animals, there may also be selection against larger genomes due to the reduced fitness associated with relatively low developmental rates and the relatively high demand for P invested in RNA (as much as 50-80% of cellular P) for protein synthesis (Hessen and Persson, 2009;Neiman et al, 2013a, but see Larkin et al, 2016). A definitive answer to the question of the extent to which larger genome sizes and higher ploidal levels translate into N and P costs will require characterization of organismlevel consequences.…”
Section: Future Research Prioritiesmentioning
confidence: 99%
“…A stoichiometric perspective leads us to speculate that genome size and ploidal level are important but often ignored functional traits. For example, very large genomes in plants could be selected against in many ecosystems due to their higher demands for N and P. In animals, there may also be selection against larger genomes due to the reduced fitness associated with relatively low developmental rates and the relatively high demand for P invested in RNA (as much as 50-80% of cellular P) for protein synthesis (Hessen and Persson, 2009;Neiman et al, 2013a, but see Larkin et al, 2016). A definitive answer to the question of the extent to which larger genome sizes and higher ploidal levels translate into N and P costs will require characterization of organismlevel consequences.…”
Section: Future Research Prioritiesmentioning
confidence: 99%
“…Females brood their offspring and give birth to crawl-away juveniles. In laboratory conditions, the snails reach maturity in 4-12 months (Winterbourn 1970;Larkin et al 2016). In natural populations, juveniles born in the spring may reach maturity in late summer, and before the next summer season, if born later in the season.…”
Section: Study Systemmentioning
confidence: 99%
“…Polyploidy is an important evolutionary phenomenon that causes the wholegenome multiplication and a consequent genomic redundancy. Both higher and lower growth rates are expected in polyploid species, based on a positive correlation with the major RNA content, and a slower metabolic rate and longer cell cycle duration, respectively (Larkin, Tucci, & Neiman, 2016;Otto, 2007). In a large-scale study of evolution of genome size in amphibians, Liedtke, Gower, Wilkinson, and Gomez-Mestre (2018) found that more rapid growth rates are associated with smaller genomes.…”
Section: Last the Relationship Between Ploidy Levels And Developmentalmentioning
confidence: 99%